A cognitive radio receiver front-end IC based on spread spectrum sensing technique - Zhang, Ying (2013)
Spectrum sensing in cognitive radio is an important part to detect unknown signal(s). This paper introduces a spread spectrum technique for spectrum sensing in cognitive radio in order to detect the availability of input spectrum within 800MHz to 3.5GHz frequency band. The designed receiver front-end IC can achieve the simulated gain of 30dB, QVCO phase noise of -117dBc/Hz at 1MHz offset at 2.4GHz carrier, noise figure of 5.3dB, IIP3 of -21dBm and total power dissipation of 90mW, including VCO and Mixer buffer.